Biomass gasification employing low-temperature carbonization pretreatment for tar reduction. (July 2019) - Umeda, Kyoe; Nakamura, Shunsuke; Lu, Ding; Yoshikawa, Kunio
Abstract: Low-temperature carbonization pretreatment for processing solid biomass provides an alternative to the standard use of raw biomass as a gasification feedstock. This low-temperature process is characterized by a comparable heating value, grindability, bulk density, and hydrophobicity to those of the standard. This study investigated the gasification characteristics of biomass carbonized at 300 °C, 350 °C, and 400 °C, and compared them to those of raw biomass from a lab-scale gasification facility with air. Response factors to changes in parameter settings were tested, such as the gasification temperature and the equivalence ratio (ER). The product gas from biomass carbonized at 300 °C had a cold gas efficiency of only 9.9% less than raw biomass and produced 57.8 wt% less tar than raw biomass. It was found that an ER of 0.2 and a gasification temperature of 1, 000 °C resulted in the optimum gasification performance for the 300 °C sample. Furthermore, the tar produced from the raw biomass, and the 300 °C sample during 500 °C pyrolysis was analyzed, and it was found that the tar produced from the raw biomass contained 27% higher molecular weight (higher than 301 g/mol), whereas the 300 °C sample contained only a 16% higher molecular weight. It is concluded that low-temperature carbonization pretreatment is effective for both gasification and the reduction of tar byproduct concentration. Highlights: Carbonized biomass syngas H2 concentration increased with increase in carbonization temperature. Carbonization pretreatment at 300 °C is effective since tar concentration is about half that from raw biomass gasification. Cold Gas Efficiency and Carbon Conversion Rate of carbonized biomass was highest at ER 0.2 and gasification temperature 1000 °C. Carbonized biomass tar products are easier to handle because of quantity and light weight.